2001
DOI: 10.1046/j.1523-1755.2001.0600031131.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria as a modifiable risk factor for the progression of non-diabetic renal disease

Abstract: The antiproteinuric effects of ACE inhibitors and lowering blood pressure are greater in patients with a higher baseline urine protein excretion. The greater beneficial effect of ACE inhibitors on renal disease progression in patients with higher baseline proteinuria can be explained by their greater antiproteinuric effects in these patients. The current level of urine protein excretion is a modifiable risk factor for the progression of non-diabetic renal disease. ACE inhibitors provide greater beneficial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
179
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(195 citation statements)
references
References 22 publications
13
179
0
3
Order By: Relevance
“…The African-American Study of Kidney Disease (AASK) recently reported that among African Americans with nondiabetic CKD, ramipril, an ACE inhibitor, was superior to a regimen that initiated therapy with either amlodipine, a dihydropyridine calcium antagonist, or metoprolol, a beta-blocker, for slowing the loss of kidney function and prevention of kidney-related clinical events (32). Furthermore, AASK study trial results were consistent with a large body of clinical trial data in nondiabetic CKD in that the greatest relative superiority of the ACE inhibitor was among those with the highest levels of proteinuria (63). Also, note that only kidney-related but not overall cardiovascular events were reported in AASK and that there was virtually no difference in BP lowering in the amlodipine and ramipril treatment arms (5).…”
Section: Evidence That Bp Lowering Slows the Progressive Loss Of Kidnsupporting
confidence: 59%
See 1 more Smart Citation
“…The African-American Study of Kidney Disease (AASK) recently reported that among African Americans with nondiabetic CKD, ramipril, an ACE inhibitor, was superior to a regimen that initiated therapy with either amlodipine, a dihydropyridine calcium antagonist, or metoprolol, a beta-blocker, for slowing the loss of kidney function and prevention of kidney-related clinical events (32). Furthermore, AASK study trial results were consistent with a large body of clinical trial data in nondiabetic CKD in that the greatest relative superiority of the ACE inhibitor was among those with the highest levels of proteinuria (63). Also, note that only kidney-related but not overall cardiovascular events were reported in AASK and that there was virtually no difference in BP lowering in the amlodipine and ramipril treatment arms (5).…”
Section: Evidence That Bp Lowering Slows the Progressive Loss Of Kidnsupporting
confidence: 59%
“…Other strategies to lower urinary protein excretion include dietary sodium restriction (66,67) as well cessation of cigarette smoking (68,69) and weight loss (70,71). Reductions in urinary protein excretion correlate with slower loss of kidney function (32,34,63). The clinician should be aware that attainment of low target BP levels (Ͻ130 to 135/80 to 85 mmHg) will be accomplished only with prescription of multiple (typically 3 to 4), not solitary, antihypertensive drugs (72).…”
Section: Evidence That Bp Lowering Slows the Progressive Loss Of Kidnmentioning
confidence: 99%
“…Large scale clinical trials and a meta analysis confirmed the benefits of ACEIs against a variety of renal diseases with their antiproteinuric effects (14, 80,81). Furthermore, recent studies demonstrated that the greater beneficial effect of ACEIs in renal disease patients with higher baseline proteinuria could be explained by the greater antiproteinuric effects in these patients (82). Thus, one of the protective mechanisms of ACEIs and ARBs is the reduction of the amount of proteinuria.…”
Section: Treatment Targeting Proteinuric Tubulointerstitial Damagementioning
confidence: 99%
“…[3][4][5][6] The presence of proteinuria, a marker of kidney damage, identifies patients at increased risk of adverse clinical outcomes, including progression to ESRD. [7][8][9][10][11][12] However, whether the effects of proteinuria on earlier signs of kidney damage, namely the rate of change in estimated GFR (eGFR), vary by baseline level of kidney function is less clear. A more detailed understanding of the relationship among proteinuria, kidney function, and progression of renal disease would permit the identification of those who are at greatest risk of a progressive decline in kidney function and aid in implementation of interventions to slow the progression or prevent the development of ESRD.…”
mentioning
confidence: 99%